LOW-COST LIDAR TLS-100 COMPARISON WITH LIDAR IPAD PRO FOR 3D MAPPING - Budisusanto, Yanto; Rizki Ubaidillah, Muchammad; Nur Cahyadi, Mokhamad; Wahyu Imani, Daud; Wahyudi Farid, Imam (Journal of Marine-Earth Science and Technology, 2021)
Currently, creating a 3D model of an object has undergone relatively rapid development, especially in technology. Several technologies that can be used to create 3D models are total stations, LiDAR, UAVs, terrestrial laser scanners, and various other products. There are also various methods for obtaining 3D models, such as aerial photogrammetry, close-range photogrammetry, terrestrial, and satellites. This study focuses on comparing the TLS-100 from aerial portraits with the iPad Pro LiDAR product from Apple Inc. The results to be analyzed are the resulting data format, the speed of data retrieval, the quality of the data obtained, and statistical analysis. This study is expected to assist in proving the quality of low-cost LiDAR and iPad Pro LiDAR products.